Leguminosenknöllchen als Nahrungsquelle heimischer Micropezidae- (Tylidae) Larven (Diptera). Zur Morphologie und Biologie der bisher unbekannten Larve von Micropeza corrigiolata L. (Tylos corrigiolatus L.). - Müller, Hubert (Contributions to Entomology = Beiträge zur Entomologie, 1957)
The egg, immature stages (1st-3rd ), and the puparium of the Palaearctic Micropeza corrigiolata L. (Micropezidae) are desribed with the aid of 20 figures. Adults were observed in a great number especially on leguminous crops from the beginning June till middle of July. The root nodules of field pea (Pisum arvense L.), red clover (Trifolium pratense L.), alfalfa (Medicago satwa L.) - in all probability also of other leguminous plants - are bored by the larvae, except only the rind. In summer most of larvae already are in the last stage, in this stage they are hibernating on leguminous crops.